The Fragile Juggernaut : Marx & Engels on Capitalism, Class Struggle and Crisis - Cleaver, Harry (Social Sciences E-Books Online, Collection 2025., 2025)
Whether loving or hating it, many visualize capitalism as an unstoppable juggernaut. For those of us who would defeat it, we must identify its weaknesses. Fortunately, Marx and Engels' writings on "crisis" reveal them. They show how its endless imposition of exploitative and alienating work creates such antagonistic conflicts everywhere as to make it, ultimately, a far more fragile monster than it first appears. Each of its efforts to shape social relationships, subordinating them to the work of commodity production and its control over society, has been and can be thrown into crisis by those of us resisting its way of life and seeking to create more appealing alternatives.